Keanekaragaman Jenis Semut (Hymenoptera: Formicidae) di Area Kebun Kelapa Sawit STKIP YPM Kabupaten Merangin Provinsi Jambi - Jesi Mustika Sari; Pitri Handayani; Andriyanto Andriyanto (Pendidikan Biologi STKIP YPM Bangko, 2019)
This research is aimed to know the variety kinds of ants in Palm Oil Garden Area. The kinds of this research was descriptive research by qualitative approach. This research was conducted on June 2019 in three steps. The first step was collecting the sample in Palm Oil Garden Area of STKIP YPM. The collecting of ants samples weredone by line transect technique, that are by using pitfall trap, hand collecting, and bait trap. The second step was ants identification that was done in Biology Laboratorium of STKIP YPM by following Identification Guide to the Ant Genera of the World (Bolton, 1994) and it was matched woth the determination key. The last step is the data analysis. The collected samples were analyzed by Shannon-Wiener diversity index (H’), index of richeness (DMg), and Evennes index (E). The result showed the ants with 1630 individuals were classified in to consisting of 10 genera and 4 subfamilies. The result of data analysis showed the value of the Shannon-Wiener diversity index (H’) is 1,8032 (medium criteria), index of richeness (DMg) is 1,2168 (low criteria), and Evennes index (E) is 0,3642 (stabil criteria)